SAFEGUARD MEASURES SEBAGAI INSTRUMEN PERLINDUNGAN INDUSTRI NASIONAL DI ERA LIBERALISASI PERDAGANGAN - Opik Sepriadi; Annie Myranika; Salman Al Ghifari; Ridwan Rais; Unggul Budi (CV. Lafadz Jaya, 2026)
International trade liberalization mandated by the World Trade Organization (WTO) requires its members to open domestic markets for goods and services from other countries. However, uncontrolled liberalization may negatively impact domestic industries, particularly when unforeseen import surges occur. In this context, safeguard measures become a crucial instrument enabling WTO member states to protect their national industries temporarily from the adverse effects of import surges. This study aims to analyze the legal framework of safeguard measures within the WTO system, their implementation in Indonesian national law, and their effectiveness as an instrument for protecting national industries in the era of trade liberalization. The research method employed is normative legal research with statutory, conceptual, and comparative approaches. The results indicate that although Indonesia has regulated safeguard measures in Government Regulation Number 34 of 2011, there are substantial weaknesses, including the absence of comprehensive specific regulations, limited outreach to industrial actors, and inconsistencies of several provisions with the WTO Agreement on Safeguards. This study recommends the establishment of a specific Trade Remedies Law that systematically integrates safeguard, anti-dumping, and countervailing measures to provide optimal legal protection for Indonesian national industries.